Limit theorem for the maximum of dependent Gaussian random elements in a Banach space - Koval, V. A.; Schwabe, R. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
The well-known Nisio result on the asymptotie equality for the maximum of real-valued Gaussian random variables is generalized to the case of Gaussian random variables taking values in a Banach space.